Structural dynamic vibration absorber using a tuned inerter eddy current damper. (1st March 2023) - Li, Dawei; Ikago, Kohju; Yin, Ao
Highlights: A tuned inerter eddy current damper (IECD) is proposed. The IECD damping mechanism is estimated using analytical methods. The results of a dynamic IECD test are discussed. A design method is developed to optimize a tuned IECD. The optimized tuned IECD is demonstrated using the results of a shake table test. Abstract: The advantages of eddy current dampers over conventional fluid dampers include the ability to produce resistive forces with no contact between the components wherein damping forces are generated, resulting in a less degradable mechanism. Thus far, the apparent mass effect, referred to as inertance, in an eddy current damper employing rotational motion has not been intentionally applied for vibration control. Therefore, this paper proposes utilizing the inertance effect in an inerter eddy current damper (IECD) to construct a dynamic vibration absorber for the seismic protection of civil structures, termed as the tuned inerter eddy current damper (TIECD). The IECD consists of a ball screw, a conductor, permanent magnets, and a back iron. The gravitational mass of the back iron disk is converted into inertance via the ball-screw mechanism, which amplifies the mass and damping effects of the rotational disk and eddy current, respectively, by converting low-speed translational motion into high-speed rotational motion. An analytical method based on the separation of variables is applied to estimate the eddy current damping force of the IECD at different velocities. Concurrently, a succinct damping model is developed to capture the mechanical behavior of the nonlinear eddy current damping. A series of dynamic tests using a small-scale prototype IECD is then conducted to confirm the feasibility and accuracy of the proposed numerical damping model. Next, an equivalent damping coefficient for eddy current damping is derived under harmonic excitation. Based on a combination of the fixed-point method, the equivalent damping coefficient of the IECD, and complex eigen analysis, an optimal design method for the TIECD is developed. Finally, the effectiveness of the proposed TIECD is validated through a shake table test and a numerical simulation.